Experimentação e aprendizagem: perspectivas da cultura de design sobre o erro capazes de auxiliar as organizações em seus processos de inovação - Fragoso, Cristiano Flores (Universidade do Vale do Rio dos Sinos, 2021)
Mistakes are ordinary situations which are part of our lives. It is well known that failures can be an opportunity for those who search for new solutions with the aim of generating innovation; but it is also recognized that mistakes carry stigmas with them. On many occasions, this situation generates a superficial view on mistakes in which the observer looks for the guilty person and does not take advantage of the opportunity for learning new lessons. Innovation and failures walk side by side. In this point, it is possible to find a real dilemma for companies: on the one hand, they try to innovate in their processes with the aim of generating better results in more and more complex and competitive markets; on the other hand, organizations avoid failings, considering them as something unproductive and negative for reaching their goals. Design, with its creative characteristics which frequently works within contexts of uncertainty, theoretically deals with failings as something positive and useful, such as a work tool. Therefore, the general goal of this research consists of identifying perspectives of the Design Culture about failures capable of helping companies in their innovation processes. Failures and their significance for the Design Culture have been investigated within three perspectives of observation: theory, designers and corporate managers. Firstly, a systematic bibliographical review about design was made with the aim of understanding how the concept of failings is defined and presented by many authors. Subsequently, experienced designers were consulted, through in-depth interviews, with the aim of showing how these professionals deal with failings in their labour market routines. From the analysis and the synthesis of the results of these first two stages of the survey, eight perspectives proposed by the Design Culture about failures were defined: connection, consequence, difficulty, motivation, opportunity, paradox, signal and recurring surprise. Within a short explanation, all of them were presented to corporate managers. Therefore, the conclusion of this research has been that the systematization proposed shows the potential for deepening the vision about failures in corporations and dealing with them in a lighter manner, providing the creation and the strength of an innovation culture in companies.
Keywords: Cultura de design; Erro; Processos de inovação; Organizações; Design culture; Failure; Innovation processes; Companies; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial